Memfasilitasi Pengembangan Potensi Diri Peserta Didik Dalam Konseling di SMP Pahlawan Nasional - Muhammad Fiqri Ramadhan; Yenti Arsini; May Syaroh Harahap (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The potential of each learner has many varieties and is different. The potential of students in each school must be developed and honed so that they can further explore the potential they desire. Based on this understanding, teachers need to work hard and creatively to explore various efforts in the form of media, teaching materials, and learning methods to facilitate students appropriately and creatively so that they are in accordance with their development, including their learning style. Self-development is actually not new for Guidance and Counseling Teachers (Guidance Teachers). So far, Guidance and Counseling Teachers have actually carried out service activities for students, which incidentally are self-development activities. This can be seen in the 2004 Competency-Based Curriculum (KBK), which states that Counseling is an assistance service for students, both individually and in groups, to be independent and develop optimally. In essence, service activities.